Metabolomic and proteomic analyses of renal function after liver transplantation - Wang, Xiaoling; Grobe, Nadja; Franchin, Barbara; Levitsky, Josh; Cravedi, Paolo; Kotanko, Peter (Frontiers in Transplantation, 2025)
BackgroundRenal dysfunction is a common and serious complication in patients with end-stage liver diseases. While some patients recover renal function after liver transplantation (LT), others do not. Additionally, patients with normal kidney function (Normal-KF) before LT may develop post-transplant renal dysfunction. Early identification of patients at risk for impaired kidney function (Impaired-KF) post-LT is critical to improving outcomes. This study integrated metabolomic and proteomic analyses to investigate molecular profiles distinguishing Normal-KF from Impaired-KF post-LT.MethodsNine LT recipients were classified into Normal-KF (n = 5) and Impaired-KF (n = 4) groups. One additional recipient with pre-transplant renal function impairment who recovered renal function after LT, was analyzed separately. Serum samples were collected at 2- and 5-weeks post-LT. The metabolomic and proteomic profiles were assessed by untargeted liquid chromatography-tandem mass spectrometry.ResultsMetabolomic analysis identified 29 significantly altered metabolites between Normal-KF and Impaired-KF (fold change > 2, p < 0.05). Proteomic analysis revealed 45 differentially expressed proteins (fold change > 1.25, p < 0.05). For the recovered patient, the metabolomic profile closely resembled Normal-KF, whereas the proteomic profile remained aligned with Impaired-KF at both 14- and 35-days post-LT. From week 2 to week 5, both the metabolomic and proteomic profiles of the recovered patient showed trends toward the Normal-KF.ConclusionThis study revealed distinct metabolomic and proteomic signatures associated with renal dysfunction post-LT. Proteomic profiles indicated a delayed recovery compared to metabolomic profiles, suggesting a dynamic and muti-layered renal recovery process. Further research is warranted to elucidate the functional implications of the differential proteins and metabolites for improved monitoring and therapeutic strategies.